Synthesis and antimycobacterial screening of new thiazolyl-oxazole derivatives - Abhale, Yogita K.; Sasane, Amit V.; Chavan, Abhijit P.; Shekh, Saddam Husen; Deshmukh, Keshav K.; Bhansali, Sujit; Nawale, Laxman; Sarkar, Dhiman; Mhaske, Pravin C. (European Journal of Medicinal Chemistry, 2017)
In the present study a series of 4-methyl-2-aryl-5-(2-aryl/benzyl thiazol-4-yl) oxazole (4a-v) have been synthesized and evaluated for their preliminary antitubercular, antimicrobial and cytotoxicity activity. Among all the synthesized compounds, 4v reported comparable activity against dormant M. tuberculosis H37Ra and M. bovis BCG strains with respect to standard drug rifampicin. The active compounds from the antitubercular study were further tested for anti-proliferative activity against HeLa, A549 and PANC-1 cell lines using MU assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antibacterial activities with MIC range of 2.1-26.8 mu g/mL. High potency, lower cytotoxicity and promising antimycobacterial activity suggested that these compounds could serve as good leads for further optimisation and development. (C) 2017 Elsevier Masson SAS. All rights reserved.

Synthesis, antimycobacterial screening and molecular docking studies of 4-aryl-4′-methyl-2′-aryl-2,5′-bisthiazole derivatives - Abhale, Yogita K.; Shinde, Abhijit D.; Deshmukh, Keshav K.; Nawale, Laxman U.; Sarkar, Dhiman; Choudhari, Prafulla B.; Kumbhar, Santosh S.; Mhaske, Pravin C. (Medicinal Chemistry Research, 2017)
A series of 4-aryl-4′-methyl-2′-aryl-2,5′-bisthia- zole derivatives (5a–o) were synthesized and screened for inhibitory activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743) strains. Five lead compounds (5e, 5f, 5g, 5h, and 5o) were further confirmed from their dose dependent effect against MTB and Bovine–Calmette–Guerin. The most promising compounds 5f (MIC90: 11.32 μg/mL), 5h (MIC90: 11.59 μg/mL), and 5o (MIC90: 23.64 μg/mL) showed strong antitubercular activity against dormant MTB and BCG as well as almost insignificant cytotoxicity up to 100μg/mL against HeLa, A549, and PANC-1 human cancer cell lines. Further, the synthesized compounds were found to have potential antibacterial activity against Gram-negative bac- teria, Escherichia coli, Pseudomonas flurescence and Gram- positive bacteria, Staphylococcus aureus, Bacillus subtilis. Most of the synthesized compounds showed moderateactivity against fungal strain Candida albicans. Molecular docking studies of these compounds showed significant interactions with crystal structure of the cytochrome P45014α-sterol demethylase (CYP51) PDB ID: 1E9X. Hydrogen bond interactions with SER261 and VAL395 are important interactions for selective inhibition of designed inhibitors. Compounds 5f, 5h, and 5o showed significant interactions with 1E9X. All the experimental results promote us to consider this series as a starting point for the devel- opment of novel, selective and more potent antitubercular agents in the future.

Synthesis of new 2-(thiazol-4-yl)thiazolidin-4-one derivatives as potential anti-mycobacterial agents - Abhale, Yogita K.; Shinde, Abhijit; Shelke, Monika; Nawale, Laxman; Sarkar, Dhiman; Mhaske, Pravin C. (Bioorganic Chemistry, 2021)
To search for potent antimycobacterial lead compounds, a new series of 3-substituted phenyl-2-(2-(substituted phenyl)thiazol-4-yl) thiazolidin-4-one (5a-t) derivatives have been synthesized by the condensation of 2 substituted phenyl thiazole-4-carbaldehyde with aromatic amine followed by cyclocondensation with thioglycolic acid. The structure of the newly synthesized 2-(thiazol-4-yl)thiazolidin-4-one derivatives were characterized by the spectroscopic analysis. The synthesized compounds were screened for antimycobacterial activity against Mycobacterium tuberculosis H37Ra (MTB) (ATCC 25177) and Mycobacterium bovis BCG (BCG, ATCC 35743). Most of the 2-(thiazol-4-yl)thiazolidin-4-one derivatives showed good to excellent antimycobacterial activity against both the Mtb strains. Nine derivatives 5c, 5g, 5j, 5m, 5n, 5o, 5p, 5s, and 5t showed excellent activity against M. bovis BCG with MIC 4.43 to 24.04 mu M were further evaluated for the cytotoxicity activity against HeLa A549, and HCT-116 cell lines and showed no significant cytotoxic activity at the maximum concentration evaluated. The potential antimycobacterial activities enforced that the thiazolyl-thiazolidin-4-one derivatives could lead to compounds that could treat tuberculosis.
Keywords: Cytotoxicity; Mycobacterium tuberculosis; Thiazole; Thiazolidin-4-one

Synthesis and antimycobacterial screening of a novel series of alpha-amino acids containing thiazole linker - Nalawade, Jitendra L.; Mhaske, Pravin C.; Shinde, Abhijit D.; Chavan, Abhijit P.; Abhale, Yogita K.; Sarkar, Dhiman; Bobade, Vivek D. (ARKIVOC, 2022)
A small focused library of uncommon (S)-2-amino-3-(4-(((4-methyl-2-arylthiazol-5-yl)methyl)amino)phenyl) propanoic acid (5a-e) and (S)-2-amino-3-(4-(((2-arylthiazol-4-yl)methyl)amino)phenyl)propanoic acid (9a-d) derivatives have been efficiently synthesized by employing molecular simplification. The title compounds were screened for inhibitory activity against Mycobacterium tuberculosis H37Ra (MTB) and Mycobacterium bovis (BCG) strains. The cytotoxicity study was conducted against primary Human Umbilical Vein Endothelial Cells (HUVECs), on two different human tumor cells HeLa, and HCT 116 and was observed non-toxic to host cells.
Keywords: Amino acid; antibacterial activity; Cytotoxicity; Mycobacterium tuberculosis; synthesis; Thiazole

Synthesis of new thiazole and pyrazole clubbed 1,2,3-triazol derivatives as potential antimycobacterial and antibacterial agents - Jagadale, Shivaji M.; Abhale, Yogita K.; Pawar, Hari R.; Shinde, Abhijit; Bobade, Vivek D.; Chavan, Abhijit P.; Sarkar, Dhiman; Mhaske, Pravin C. (Polycyclic Aromatic Compounds, 2022)
New series of 4-methyl-2-(4-substituted phenyl)-5-(4-((4-(4-substituted phenyl)-1H-1,2,3-triazol-1-yl)methyl)-1-phenyl-1H-pyrazol-3-yl)thiazole, 6a-t and 4-(1,3-diphenyl-1H-pyrazol-4-yl)-1-((1,3-diphenyl-1H-pyrazol-4-yl)methyl )-1H-1,2,3-triazole, 11a-o derivatives have been synthesized by applying copper-catalyzed [3 + 2] cycloaddition reaction. The newly synthesized 1,3-thiazolyl-pyrazolyl-1,2,3-triazole (6a-t) and bis-pyrazolyl-1,2,3-triazole (11a-o) derivatives were screened for in vitro antimycobacterial activity against M. Tuberculosis H37Ra dormant and active and antibacterial activity against four pathogenic bacteria, E. coli (NCIM 2576), P. flurescence (NCIM 2059), S. aureus (NCIM 2602) and B. subtilis (NCIM 2162). Compounds 6a, 6f, 6j, 11e and 11m showed good activity against M tuberculosis H37Ra Active strain, also compounds 6g, 6h, 11f, 11n and 11o showed good activity against M tuberculosis H37Ra Dormant strain. Compounds 6b, 6i, 6l, 6o, 6r, 11k, 11l and 11m showed good activity against B. subtilis with IC50 1.99-2.96 mu g/mL. The antibacterial activity of thiazolyl-pyrazolyl-1,2,3-triazole and bis-pyrazolyl-1,2,3-triazole derivatives suggested that, these derivatives could lead to new compounds for treatment against bacterial infection.
Keywords: 123-Triazole; antibacterial activity; antimycobacterial activity; Pyrazole; Thiazole

Synthesis and antimicrobial evaluation of novel 2'-aryl-4-aryl-2,4'-Bisthiazole and 2'-aryl-4-Pyridyl-2,4'-bisthiazole derivatives as potential antibacterial agents - Nalawade, Jitendra; Shinde, Abhijit; Abhale, Yogita K.; Nandurkar, Yogesh; Bobade, Vivek D.; Sarkar, Dhiman; Mhaske, Pravin C. (Polycyclic Aromatic Compound, 2024)
In continuation of our research work to explore bisthiazole derivatives as potential antimicrobial agents, herein we reported the synthesis of a series of novel 2'-aryl-4-aryl-2,4'-bisthiazole (7a-t) and 2'-aryl-4-pyridyl-2,4'-bisthiazole (9a-l) by cyclocondensation of 2-aryl thiazole-4-carbothioamide 5a-d with 2-bromo-1-arylethanone (6a-e) and bromo-1-(pyridin-2/3/4-yl)ethanone (8a-c), respectively. These novel candidates were evaluated in vitro for their antibacterial potential against four pathogenic bacteria, Escherichia coli (NCIM 2576), Pseudomonas flurescence (NCIM 2059), Staphylococcus aureus (NCIM 2602), and Bacillus subtilis (NCIM 2162). The synthesized compounds were also screened for their in vitro antifungal activity against Candida albicans (NCIM 3100). Among them, compounds 7b, 9d, 9 g, 9i, and 9 l exhibited excellent antibacterial activity with MIC 2.1 to 12.3 mu g/mL against all tested strains. Most of the compounds reported moderate antifungal activity. The pyridine ring-substituted bisthiazole reported good to excellent antibacterial activity as compared to phenyl ring-substituted bisthiazole. The potential antibacterial activity suggested that bisthiazole derivatives could assist in the development of lead compounds to treat microbial infections.
Keywords: 24'-bisthiazole; antibacterial activity; Antifungal activity; cyclocondensation